Mini-review of hair cortisol concentration for evaluation of Cushing syndrome. Issue 5 (3rd September 2018) - Hodes, Aaron; Meyer, Jerrold; Lodish, Maya B.; Stratakis, Constantine A.; Zilbermint, Mihail
ABSTRACT: Introduction : The diagnosis of endogenous Cushing syndrome is often challenging and requires multiple repeated blood, urine, and saliva tests to detect elevated cortisol levels. Hair cortisol concentration has been described as a marker of long-term exposure to systemic cortisol in patients with Cushing syndrome. Like hemoglobin A1c is used to detect serum glucose exposure over months, segmental hair cortisol can help identify patients with milder forms of and/or periodic or cyclical Cushing syndrome, which may reduce time and costs associated with collection of urine, salivary, and serum cortisol. Areas covered : Success of hair cortisol in detection of Cushing syndrome will be discussed in context of current literature, including differences between total or segmental hair cortisol in accurately determining timeline of cortisol exposure. Optimal methods of hair collection, storage, processing, and analysis and efforts toward standardization will be a major focus. Expert commentary : Recent evidence suggests increased sensitivity and specificity of hair cortisol in detecting Cushing syndrome. Future guidelines should consider this test as a routine part of the repertoire of screening tests for Cushing syndrome. Possible confounders to explain discrepant results in the literature will be discussed.